THE DEVELOPMENT OF A PROBLEM-BASED LEARNING-BASED E-WORKSHEET ASSISTED BY LIVEWORKSHEETS TO ENHANCE STUDENTS’ LEARNING MOTIVATION IN ELEMENTARY SCHOOL - Ika Okta Kirana; Fitri Anggraini (Fakultas Keguruan dan Ilmu pendidikan (FKIP) Universitas Labuhan Batu, 2026)
Elementary school students' learning motivation remains a challenge, especially in learning that has not integrated interactive media with an appropriate pedagogical approach. Although E-LKPD and Problem Based Learning (PBL) have been widely studied, empirical evidence regarding the effectiveness of their integration on learning motivation is still limited. This study aims to examine the effect of PBL-based E-LKPD on student learning motivation. This study used a quasi-experimental design with 60 fifth-grade students of MIS Al Khoirot who were divided into two groups (experimental and control classes). The research instrument was a learning motivation questionnaire (20 items; α = 0.89). Data analysis included paired sample t-test, independent sample t-test, N-Gain, and effect size. The results showed a higher increase in learning motivation in the experimental class (65.40 to 82.30) compared to the control class (66.10 to 72.50). The difference between groups was significant (t = 5.42; p < 0.001) with a moderate N-Gain (0.68) in the experimental class and a low N-Gain (0.28) in the control class. An effect size of 1.10 indicates a large influence. These findings confirm that the integration of E-LKPD and PBL effectively increases learning motivation and provides a new contribution to the development of problem-based learning media in elementary schools.